Modeling drivers of postharvest losses among smallholder vegetable farmers in eThekwini Metropolitan: an examination of a zero-inflated Poisson (ZIP) approach - Siphesihle Qange; Lelethu Mdoda; Asanda Mditshwa (Cogent Food & Agriculture)
Postharvest losses (PHLs) challenge smallholder vegetable farmers in developing countries, notably in sub-Saharan Africa, impacting food security and economic sustainability. Despite efforts to mitigate PHLs, understanding remains insufficient. This knowledge gap hinders the development and implementation of effective interventions. Therefore, this study investigated the key drivers of postharvest losses among smallholder vegetable farmers in eThekwini Municipality. The study adopted a cross-sectional research design and multi-stratified random sampling technique to gather primary data from 238 smallholder vegetable farmers through structured questionnaires. Descriptive statistics and zero-inflated Poisson (ZIP) Regression were used for analysis. Descriptive statistics indicated that female farmers were dominant (56%), with an average age of 45 years and an average household size of six individuals. On average, farmers have completed 12 years of schooling, and a significant portion, comprising 76%, were unemployed. The primary source of income for farmers (78%) was derived from farming activities. The ZIP model indicated that age and household size were significant at the 5% level, while years in school, farm experience, extension service, labor, storage, distance to the market, and weather conditions were significant at the 1% level. Thus, the study recommends improving extension services and capacity-building to improve agricultural productivity and reduce PHLs.